Signs of political contacts between Lithuanian and Polish emigrants in 1940–1990 - Banionis, Juozas (Genocidas ir rezistencija, 2018)
After annexation of Lithuania by the USSR in 1940, Lithuanian political diaspora in Western countries actively joined the movement for Lithuania’s liberation. Maintenance of relations with emigrants from Eastern and Central European countries, which became dependent on the Soviets, was considered as one of the factors of its enhancement. All this had to contribute to consolidation of powers of all the nations of the aforesaid part of Europe, which were united by the similar goal: to seek liberation and restoration of independence of their homelands. Next to close collaboration with Latvians and Estonians, who shared common destiny, the contacts of Lithuanians with Polish, their historical neighbours, were of utmost importance. Lithuanian-Polish contacts in the West may be described from three perspectives. Firstly, meetings of Lithuanian political leaders with representatives of the Polish government in exile have to be mentioned. Secondly, exchange of opinions between Lithuanian emigrant organisations and relevant Polish institutions in the West is important as well as communication of Lithuanian emigrants with famous Polish personalities in emigration. In the 1940s (1947) already, Vaclovas Sidzikauskas, a representative of the Supreme Committee for the Liberation of Lithuania (VLIK), which consistently protected the right of Lithuania’s sovereignty abroad, established relations with Adam Tarnowski, a representative of Polish government in exile. The emphasis was laid on the common goal of both nations to restore the independence and on purely peaceful solution to contentious issues. In the 1950s the relations between the Committee for Free Lithuania (LLK) set up in the USA and Polish Political Council (Polska Rada Polityczna) were established. For example, during the meeting of 18 January 1954 they discussed international situation, evaluated the Soviet policies and discussed perspectives of liberation of Lithuania and Poland. Individual initiatives, which promoted the dialogue between Lithuanians and Polish, were also frequent. As early as the middle of the 1950s, the Polish journal “Kultura” published in Paris, already contained articles about perspectives of coexistence of Lithuanian and Polish nations written by Juozas Girnius, Jerzy Giedroyc, Jerzy Iwanowski, Tadeusz Kotelbach, and later by Czesław Miłosz, Zdzisław Rurarz and Tomas Venclova. The relation between Lithuanian and Polish emigrants never seized during the whole period of Lithuania’s liberalisation movement in the West. In the 1970s (October 1978), even before emergence of “Solidarity”, J. Giedroyc met Dr. Juozas K. Valiūnas, Chairperson of VLIK, in Paris. Then the idea of signing the declaration of friendship between Lithuanians and Polish was put forward. In the 1980s, when liberation of Poland and later that of Lithuania were becoming more and more realistic, the agendas of both nations started embracing the relevant issues of dependence of Vilnius region, Archdiocese of Vilnius, Western Ukraine and Belarus and it is not by chance that these issues were also included into the agenda of the Yalta Conference. The most active participants in the discussions were new social-political organisation “Pomost” on the Polish side and the World Lithuanian Community (PLB) on the Lithuanian side. The aspirations of the Lithuanian and Polish nations were expressed in the most moderate way through the Assembly of Captive European Nations (ACEN) founded in the USA in 1954 and consisting of Eastern and Central European nations. The latter organisation, which regularly organised meetings with the US Administration and clearly determined the goals of the nations, significantly contributed to formation of moral and political support from the West and strengthening of movement of resistance against soviet dependence in Eastern Europe. Generalising, it can be stated that political organisations, which actively participated in the movement for Lithuania’s liberation in the West, maintained contacts with Polish institutions in emigration and built bridges for future alliance of free states of Lithuania and Poland.